PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA DAN NILAI PERUSAHAAN - Citra Sari; Hersugondo Hersugondo (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2023)
The research was conducted to determine the relationship between corporate social responsibility (CSR) in the Indonesian banking sector, along with CSR disclosure practices and their impact on financial performance and firm value. From 2016 to 2020, relevant data were gathered from bank annual reports and sustainability reporting, financial sites, and the Indonesia Stock Exchange (IDX). Multiple regression analysis with the constant-coefficient model was used in this research (OLS). The findings indicate that commercial banks are involved in CSR activities, and appropriate disclosures have helped improve accounting-based financial performance as indicated by return of equity (ROE), return of assets (ROA), and corporate value based EPS and Tobin's Q. The research findings contribute to a better understanding of CSR practices in developing countries' financial sectors, which are making dynamic efforts to develop their financial culture and can promote rapprochement with the Indonesian financial sector.